Cemil [Topuzlu] Paşa’nın belediye başkanlıkları ve İstanbul’daki imar faaliyetleri - Kara, Hatice (My University)
Bu çalışmada XIX. yüzyılın son çeyreğinden XX. yüzyılın ilk yarısına kadar şehircilik, kültür, sanat, tıp gibi alanlarda önemli faaliyetlerde bulunmuş, başarılarıyla ülkemizi dünya çapında temsil etmiş, İstanbul’da iki dönem belediye başkanlığı yaparak, Osmanlı başkentinin imarında önemli rol oynamış olan Cemil Paşa’nın hayatı ele alınmıştır. Cemil Paşa gerek Avrupa’da eğitim alması ve gerek hanedan ailesine yakınlığı ile siyasi bağlantıları sayesinde pek çok radikal kararlar almıştır. Başarılı bir hekim olan Cemil Paşa, başkent İstanbul’u Avrupa’daki diğer başkentler gibi modern bir hâle getirmeye çalışmıştır. İyi bir belediyeci ve tıp doktoru olan Cemil Paşa idari, kültürel ve bilimsel hayatımızın önemli isimleri arasında yer almaktadır. Cemil Paşa, Cemil Topuzlu, Şehremini, İstanbul, Nafia Nazırlığı, Tıp Tarihi.

This study focuses on the life of Cemil Pasha, who, as an important Ottoman figure from the last quarter of 19th century to the first half of the 20th century, had important achievements in city planning, culture, arts and medicine, represented our country successfully in international arena, served as the mayor of Istanbul for two terms and played a significant role in the development of the Ottoman capital during his terms. Cemil Pasha made many radical decisions due to both his European education and his close relationship with the Ottoman dynasty that allowed him to develop important political connections. Cemil Pasha played a significant role in transforming Istanbul into a modern capital city comparable to European capitals. As a successful medical doctor and mayor Cemil Pasha is one of the most pioneering actor in the administrative, cultural and scientific history of the Ottoman Empire. Key Words: Cemil Pasha, Cemil Topuzlu, Mayor, İstanbul, Ministry of Public Works, Medical History.
Keywords: Biyografi; Topuzlu, Cemil, 1868-1958